The Overview of Caregiver Burden in Families with Hemodialysis Patient - Salsabila, Nada; Pratiwi, Sri Hartati; Emaliyawati, Etika (Indonesian Journal of Global Health Research, 2024)
Chronic renal failure patients undergoing haemodialysis therapy experience various conditions and require long-term care which can cause a burden on the families who care for patients. This family caregiver burden can affect the quality of life of both patients and family caregivers, and also affect the care provided to patients. The purpose of the study was to determine the description of caregiver burden in families with haemodialysis patients. This study is a quantitative descriptive study and the sample was taken using purposive sampling technique (n = 107) with the inclusion criteria of respondents as the main caregiver with family members undergoing haemodialysis therapy at RSUD Sumedang, and physically and mentally healthy. Exclusion criteria in the study were potential respondents who refused to participate and respondents who decided to stop in the middle of the study. The burden of caregivers on the family was measured using the Burden Scale for Family Caregivers Short Scale (BSFC-s) questionnaire with test results, namely r results (0.634) > r table (0.786) as well as Cronbach alpha value of 0.900 which means this questionnaire is valid and reliable. The picture of caregiver burden shows that almost half of family caregivers are in the high category (49.5%) and most experience heavy burden in the physical dimension. The results of this study are expected to be used as a reference for learning and evaluation for nurses, family caregivers, and educational institutions to be able to carry out effective interventions that can be carried out to reduce the burden of care experienced by family caregivers.